Analysis of Investment Interest of Jakarta’s Business Actors to Invest at the National Capital of Nusantara - Purnama, Suryadi Jaya; Triwiyanto, Askar; Chotib, Chotib (UI Scholars Hub, 2024)
Background: The existence of opportunities for business actors to invest must be balanced with incentive policies to provide an attraction for business actors to invest in the new national capital so that they can create new jobs so that economic recovery occurs while increasing Gross Regional Domestic Product (GRDP). Aims: This research was conducted in Jakarta and its surroundings and aims to analyze the development of investment interest and the factors that influence the business world in investing in The Capital City of Nusantara. Methods: This research was carried out using path analysis using multiple linear regression techniques using data processing based on SPSS 26 software and comparing it with the Partial Least Square (PLS) model. Results: Hypothesis testing shows consistent results that political, economic, environmental factors as well as trust factors have an appropriate and significant relationship with investment interest in The Capital City of Nusantara. Meanwhile, government policy factors and social factors do not have a significant relationship with investment interest in The Capital City of Nusantara. political, government policy, social, economic and environmental factors have a significant positive relationship with trust. The Sobel test shows that the trust variable is an intervening factor in the influence of economic, government policy, environmental and social variables on investment interest. Conclusion: Evaluation and analysis of laws and regulations related to moving the country's capital need to be the next research that will complement this research.